2004
DOI: 10.1098/rspb.2004.2711
|View full text |Cite
|
Sign up to set email alerts
|

Sex–biased maternal investment in voles: importance of environmental conditions

Abstract: Adaptive bias in sex allocation is traditionally proposed to be related to the condition of mothers as well as to the unequal fitness values of produced sexes. A positive relationship between mother condition and investment into male offspring is often predicted. This relationship was also recently found to depend on environmental conditions. We studied these causalities experimentally using a design where winter food supply was manipulated in eight outdoor-enclosed populations of field voles Microtus agrestis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…The very early age of pups reported in our study (<1 month) suggests that sex-biased maternal investment takes place at the stage of conception, mortality in utero, and (or) during the first few weeks following birth. Sex-biased maternal investment has not been studied so far in canids, although it was investigated in ungulates (review in Hewison and Gaillard 1999), primates (e.g., Brown 2001;Ostner et al 2005), and rodents (e.g., Koskela et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The very early age of pups reported in our study (<1 month) suggests that sex-biased maternal investment takes place at the stage of conception, mortality in utero, and (or) during the first few weeks following birth. Sex-biased maternal investment has not been studied so far in canids, although it was investigated in ungulates (review in Hewison and Gaillard 1999), primates (e.g., Brown 2001;Ostner et al 2005), and rodents (e.g., Koskela et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the beneficial effects of large egg size on offspring body size could be more pronounced in female offspring when it influences their future fecundity (Falconer 1965) or in male offspring when it influences their attractiveness or competitive ability (Trivers & Willard 1973). In this vein, female field voles Microtus agrestis produce larger males when environmental conditions are good, whereas no such pattern is observed for female offspring (Koskela et al . 2004).…”
Section: Environmental Dependency Of Maternal Effectsmentioning
confidence: 99%
“…This concurs with the results of Kager and Fietz (2009), who found that litter size in edible dormice increased with the degree of seed mast and in response to continuous supplemental feeding. For some small mammal species food supplementation results in no increase in litter size (Hubbs and Boonstra 1997;Koskela et al 2004;O'Donoghue and Krebs 1992) or only a slightly larger litter size (Karels et al 2000). Provided that reproduction is limited by food availability, this indicates that in these species the reproductive value of the offspring does not vary much between years, probably due to a relatively constant food supply and thus constant survival probability for the young.…”
Section: Discussionmentioning
confidence: 95%
“…Food availability is one of the most important factors affecting reproduction (Hubbs and Boonstra 1997;Karels et al 2000;Koskela et al 1998Koskela et al , 2004. Food resources are typically not distributed uniformly, but vary on a spatial and temporal scale.…”
mentioning
confidence: 99%